Effects of Evolocumab Added to Moderate-Intensity Statin Therapy in Chinese Patients With Acute Coronary Syndrome: The EMSIACS Trial Study Protocol - Gao, Jing; Liu, Jing-Yu; Lu, Peng-Ju; Xiao, Jian-Yong; Gao, Ming-Dong; Li, Chang-Ping; Cui, Zhuang; Liu, Yin (Frontiers in Physiology, 2021)
Background: Several studies have demonstrated that using a higher dose of statin can easily induce liver injury and myopathy. Low-density lipoprotein cholesterol (LDL-C) is a well-established modifiable risk factor for cardiovascular disease; however, the large majority of Chinese patients cannot meet the target level of LDL-C recommended by the Chinese expert consensus. Evolocumab has been demonstrated to reduce LDL-C by approximately 60% in many studies. Nevertheless, whether combine evolocumab and moderate-intensity statin is as effective in lowering LDL-C and decrease incidence of MACE in Chinese patients presenting with the acute phase of acute coronary syndrome (ACS) remains unknown. Therefore, the “Evolocumab added to Moderate-Intensity Statin therapy on LDL-C lowering and cardiovascular adverse events in patients with Acute Coronary Syndrome” (EMSIACS) is conducted. Methods: The EMSIACS is a prospective, randomized, open-label, parallel-group, multicenter study involving analyzing the feasibility and efficacy of evolocumab added to moderate-intensity statin therapy on lowering LDL-C levels in adult Chinese patients hospitalized for acute phase ACS. The sample size calculation is based on the primary outcome and 500 patients will be planned to recruit. Patients are randomized in evolocumab arm (evolocumab 140 mg every two weeks plus rosuvastatin 10 mg/day or atorvastatin 20 mg/day) and statin-only arm (rosuvastatin 10 mg/day or atorvastatin 20 mg/day). The primary outcome is the percentage change in LDL-C in weeks 4 and week 12 after treatment. The secondary outcome is the occurrence of MACE after 12 weeks and 1 year of treatment. Discussion: If the EMSIACS trial endpoints prove statistically significant, the evolocumab added to moderate-intensity statin therapy will have the potential to effectively lower subjects’ LDL-C levels, especially for the Chinese patients with acute phase ACS. However, if the risk of MACE is not significantly different between the two groups, we may extend follow-up time for secondary outcome when the clinical trial is over. Trial registration: The study is registered to ClinicalTrials.gov (NCT04100434), which retrospectively registered on November 24, 2020.